Addicted to cheap shopping - Telling, Leo (Australia : BBC, 2007)
In this program host Libby Potter travels around the world as she takes a meaningful look at the economics behind inexpensive goods for sale in big-box stores and malls. Cost-cutting through supply chain management and waste reduction, economies of scale achieved by shipping offshore-manufactured goods to market via super-container ships, the Wal-Mart effect, and the no-frills philosophy of IKEA are addressed
Title from title screen
Camera, Jonathan Young, Paul Cox, Mark Johnson ; editor, Damian Leask ; assistant producer, Samuel Goss ; executive producer, Paul Woolwich
Presenter, Libby Potter
DVD format
Keywords: Ikea (Firm); Wal-Mart (Firm); Economies of scale; Retail trade; Discount houses (Retail trade); Wal-Mart (Firm)